PENGEMBANGAN E-LKPD PERTUMBUHAN DAN PERKEMBANGAN TUMBUHAN BERBASIS PENDEKATAN PEMBELAJARAN MENDALAM UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS MURID - Nur Cahya, Elva; Wisanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an Electronic Student Worksheet (E-worksheet) on plant growth and development based on a deep learning approach that is feasible to train the critical thinking skills of Grade XI high school students. This study employed the 4D development model (Define, Design, Develop, Disseminate) and was conducted at SMA Negeri 1 Gresik involving 30 Grade XI students. The feasibility of the E-worksheet was analyzed based on three aspects: validity, practicality, and effectiveness. Validity was assessed by two validators using the Aiken index, practicality was obtained from implementation observations and student response questionnaires, while effectiveness was analyzed through a paired sample t-test, N-gain calculation, and the attainment of critical thinking indicators. The results showed that (1) the validity of the E-worksheet obtained an average Aiken index of 0.99 in the valid category; (2) the practicality of the E-worksheet obtained an implementation percentage of 98.3% and student response of 95.1% in the very practical category; and (3) the effectiveness of the E-worksheet was evidenced by a paired sample t-test significance value of 0.000 (< 0.05), an average N-gain of 0.85 in the high category, and the attainment of all critical thinking indicators with an average score of ≥ 76 in the good to very good category. Based on these results, the E-worksheet on plant growth and development based on a deep learning approach is declared feasible and effective for training students' critical thinking skills.